Etiology, outcome and prognostic indicators of childhood fulminant hepatic failure in the United Kingdom - Lee, Way Seah; McKiernan, P.; Kelly, D.A. (Lippincott, Williams & Wilkins, 2005)
Objective: To study the etiology, outcome and prognostic indicators in children with fulminant hepatic failure in the United Kingdom. Design: Retrospective review of all patients < 17 years with fulminant hepatic failure from 1991 to 2000. Fulminant hepatic failure was defined as presence of coagulopathy (prothrombin time > 24 seconds or International Normalized Ratio > 2.0) with or without hepatic encephalopathy within 8 weeks of the onset of symptoms. Setting: Liver Unit, Birmingham Children's Hospital, United Kingdom. Results: Ninety-seven children (48 male, 49 female; median age, 27 months; range, 1 day-192.0 months) were identified with fulminant hepatic failure. The etiologies were: 22 metabolic, 53 infectious, 19 drug-induced, and 3 autoimmune hepatitis. The overall survival rate was 61. 33 (32/97) recovered spontaneously with supportive management. Fifty-five children were assessed for liver transplantation. Four were unstable and were not listed for liver transplantation; 11 died while awaiting liver transplantation. Liver transplantation was contraindicated in 10 children. Of the 40 children who underwent liver trans-plantation, 27 survived. Children with autoimmune hepatitis, paracetamol overdose or hepatitis A were more likely to survive without liver transplantation. Children who had a delay between the first symptom of liver disease and the onset of hepatic encephalopathy (median, 10.5 days versus 3.5 days), higher plasma bilirubin (299 mu mol/L versus 80 mu mol/L), higher prothrombin time (62 seconds versus 40 seconds) or lower alanine aminotransferase (1288 IU/L versus 2929 IU/L) levels on admission were more likely to die of fulminant hepatic failure or require liver transplantation (P < 0.05). On multivariate analysis, the significant independent predictors for the eventual failure of conservative therapy were time to onset of hepatic encephalopathy > 7 days, prothrombin time > 55 seconds and alanine aminotransferase <= 2384 IU/L on admission. Conclusions: Children with fulminant hepatic failure with severe coagulopathy, lower alanine aminotransferase on admission and prolonged duration of illness before the onset of hepatic encephalopathy are more likely to require liver transplantation. Early referral to a specialized center for consideration of liver transplantation is vital. (c) 2005 Lippincott Williams & Wilkins.